A Cross Sectional Study for Assessment of the Pattern of Partial Edentulism in Various Municipalities of Kavre District - Basnyat, S KC; Prajapati, D; Mahanta, S (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Partial edentulism refers to missing one or more natural teeth but not all. Classifying the partial edentulous arches is necessary as it helps in treatment planning, designing and recognition of prosthetic support for removable partial denture. The main aim of this study was to access patterns of partial edentulism among patients and determine its association with socio-demographic parameters.Methods: Patients from various municipalities of Kavre district were selected for the study. Total of 206 patients were selected. The study was divided into two part. Questionnaire related to demographic data and intraoral examination to evaluate the pattern of partial edentulism according to Kennedy's Classification and Applegate's rule. The chi-square test was used to determine the association between Socio-demographic variables and pattern of partial edentulism. Statistical evaluation will be done using the Statistical Package for Social Sciences (SPSS 20.0), the level of significance set at p-value